Design, performance evaluation and analysis of the inlet tube of pressure sensor for chamber pressure measurement. Issue 4 (15th July 2019) - Gobi, K.; Kannapiran, B.; Devaraj, D.; Valarmathi, K.
Abstract : Purpose: In Aerospace applications, the inlet tubes are used to mount strain gauge type pressure sensors on the engine under static test to measure engine chamber pressure. This paper aims to focus on the limitations of the inlet tube and its design aspects to serve better in the static test environment. The different sizes of the inlet tubes are designed to meet the static test and safety requirements. This paper presents the performance evaluation of the designed inlet tubes with calibration results and the selection criteria of the inlet tube to measure combustion chamber pressure with the specified accuracy during static testing of engines. Design/methodology/approach: Two sensors, specifically, one cavity type pressure sensor with the inlet tube of range 0-6.89 MPa having natural frequency of the diaphragm 17 KHz and another flush diaphragm type pressure sensor of the same range having −3 dB frequency response, 5 KHz are mounted on the same pressure port of the engine under static test to study the shortcomings of the inlet tube. The limitations of the inlet tube have been analyzed to aid the tube design. The different sizes of inlet tubes are designed, fabricated and tested to study the effect of the inlet tube on the performance of the pressure sensor. The dynamic calibration is used for this purpose. The dynamic parameters of the sensor with the designed tubes are calculated and analyzed to meet the static test requirements. The diaphragm temperature test is conducted on the representative hardware of pressure sensor with and without inlet tube to analyze the effect of the inlet tube against the temperature error. The inlet tube design is validated through the static test to gain confidence on measurement. Findings: The cavity type pressure sensor failed to capture the pressure peak, whereas the flush diaphragm type pressure sensor captured the pressure peak of the engine under a static test. From the static test data and dynamic calibration results, the bandwidth of cavity type sensor with tube is much lower than the required bandwidth (five times the bandwidth of the measurand), and hence, the cavity type sensor did not capture the pressure peak data. The dynamic calibration results of the pressure sensor with and without an inlet tube show that the reduction of the bandwidth of the pressure sensor is mainly due to the inlet tube. From the analysis of dynamic calibration results of the sensor with the designed inlet tubes of different sizes, it is shown that the bandwidth of the pressure sensor decreases as the tube length increases. The bandwidth of the pressure sensor with tube increases as the tube inner diameter increases. The tube with a larger diameter leads to a mounting problem. The inlet tube of dimensions 6 × 4 × 50 mm is selected as it helps to overcome the mounting problem with the required bandwidth. From the static test data acquired using the pressure sensor with the selected inlet tube, it is shown that the selected tube aids the sensor to measure the pressure peak accurately. The designed inlet tube limits the diaphragm temperature within the compensated temperature of the sensor for 5.2 s from the firing of the engine. Originality/value: Most studies of pressure sensor focus on the design of a sensor to measure static and slow varying pressure, but not on the transient pressure measurement and the design of the inlet tube. This paper presents the limitations of the inlet tube against the bandwidth requirement and recommends dynamic calibration of the sensor to evaluate the bandwidth of the sensor with the inlet tube. In this paper, the design aspects of the inlet tube and its effect on the bandwidth of the pressure sensor and the temperature error of the measured pressure values are presented with experimental results. The calibration results of the inlet tubes with different configurations are analyzed to select the best geometry of the tube and the selected tube is validated in the static test environment.